Causes Of Stress and Modern Psychological Solutions - Baqoyeva Zarina Rayimovna (Genius Journals, 2022)
This article discusses the mental problems of people, stress, which is one of the main problems of today. However, the article also cites a number of solutions based on the general information obtained.
Keywords: Stress; World Health Organization; allergy; psychoanalysis